2006
DOI: 10.1242/dev.02675
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signaling promotes regional specification by negatively regulatingwinglessexpression inDrosophila

Abstract: During development, a small number of conserved signaling molecules regulate regional specification, in which uniform populations of cells acquire differences and ultimately give rise to distinct organs. In the Drosophila eye imaginal disc, Wingless (Wg) signaling defines the region that gives rise to head tissue. JAK/STAT signaling was thought to regulate growth of the eye disc but not pattern formation. However, we show that the JAK/STAT pathway plays an important role in patterning the eye disc: it promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(134 citation statements)
references
References 60 publications
8
125
1
Order By: Relevance
“…Eya RNAi (Figure 4, B and F), suggesting endogenous signaling is limited and insufficient to activate the extra Stat protein. Consistent with this interpretation, previous reports have shown that although UAS-Stat can rescue Stat92E null phenotypes, its overexpression in an otherwise wild-type background does not perturb eye development (Ekas et al 2006).…”
Section: Mathey-prevot 2002;supporting
confidence: 74%
“…Eya RNAi (Figure 4, B and F), suggesting endogenous signaling is limited and insufficient to activate the extra Stat protein. Consistent with this interpretation, previous reports have shown that although UAS-Stat can rescue Stat92E null phenotypes, its overexpression in an otherwise wild-type background does not perturb eye development (Ekas et al 2006).…”
Section: Mathey-prevot 2002;supporting
confidence: 74%
“…Another regulator of wg expression is the JAK/STAT signaling pathway. The ligand Unpaired (Upd) is expressed at the posterior margin of the early eye disc and promotes the formation of the eye field through repression of wg transcription (37,38). The negative regulatory interactions between anteriorly expressed Wg and posteriorly expressed signaling molecules including Hh, Dpp and Upd thus define the boundaries of the eye field.…”
Section: Wg Inhibits Eye Specificationmentioning
confidence: 99%
“…A presentation as well as a recent paper from Erika Bach's laboratory concentrated specifically on a developmental patterning role for Upd through the Jak/Stat pathway. 8 They suggest a role for Jak/Stat in establishing the proximal-distal axis in the developing leg and antennal imaginal discs. They show that Upd is expressed in a pattern complementary to Wingless expression.…”
Section: Jak/stat Signalingmentioning
confidence: 99%
“…Furthermore, they have shown that in the developing eye imaginal disc Jak/Stat has a patterning function in addition to the previously identified effects on cell proliferation. 8 In addition, they have found that an as yet unidentified cell-autonomous factor functions downstream of Stat to repress Wg expression in imaginal discs. This study implies that much remains to be learned about Jak/Stat signaling in development, and suggests that-by conveying contextspecific signals for stemness, proliferation or differentiation-Jak/Stat is not different from other developmental pathways.…”
Section: Jak/stat Signalingmentioning
confidence: 99%
See 1 more Smart Citation